Assessment of lead (Pb) residues in organs and muscles of slaughtered pigs at Nsukka and Environs in Enugu state, Nigeria (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: Heavy metals are serious environmental pollutants and their uptake and accumulation in the ecosystem, beyond safe limits, would cause direct consequences to food chain and ultimately to man. The present study was undertaken to ascertain the presence and levels of lead (Pb) in muscles and organs of slaughtered pigs at Nsukka agricultural zone, Nigeria.Materials and methods: From a total of 160 slaughtered pigs, liver, kidney and muscle of each pig were collected and processed for the detection of lead residue using Atomic Absorption Spectrophotometer.Results: A prevalence rate of 81.25% was recorded for Pb residue in Nsukka agricultural zone. There is a strong association (P